2016
DOI: 10.1016/j.jcot.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The indications for major limb amputations: 8 years retrospective study in a private orthopaedic and trauma centre in the south-east Nigeria

Abstract: Traumatic gangrene and other trauma related limb conditions are the leading indications for amputation in this study despite some recent reports stating otherwise. Trauma is largely preventable and so there is a need for continued intensification of the public campaign on road use as a means of preventing severe limb injuries and thus reducing consequent need for amputations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
0
12
1
Order By: Relevance
“…Diabetes care in LMICs especially those in sub-Saharan Africa (SSA) is beset with inherent organisational deficits including fragmentation of care, inadequate allocation of resources and unwavering attention to achieving glycemic targets [14, 15]. These factors have contributed to an increasing burden of complications prominent among them foot disorders [16, 17]. Although a high burden of non-traumatic LLA has recently been reported in Ghana [18], the role of diabetes on this burden is yet to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes care in LMICs especially those in sub-Saharan Africa (SSA) is beset with inherent organisational deficits including fragmentation of care, inadequate allocation of resources and unwavering attention to achieving glycemic targets [14, 15]. These factors have contributed to an increasing burden of complications prominent among them foot disorders [16, 17]. Although a high burden of non-traumatic LLA has recently been reported in Ghana [18], the role of diabetes on this burden is yet to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Two hospital-based studies in Nigeria have demonstrated that diabetic foot disease accounted for the majority of non-traumatic amputations performed, ranging from 22.3% to 29.3% 5,6. The combination of neuropathy, ischaemia and direct adverse effects of DM on hosts defense mechanisms make patients with diabetes particularly vulnerable to foot infections and gangrene; often resulting in limb loss 7.…”
Section: Introductionmentioning
confidence: 99%
“…The limit of our study is its retrospective character and the small sample size despite a long study period. This number reflects the rarity of this indication in our current trauma and its low frequency in the literature gives this series of [11].…”
Section: Discussionmentioning
confidence: 67%